2002
DOI: 10.1073/pnas.152241199
|View full text |Cite
|
Sign up to set email alerts
|

A hemocyanin from the Onychophora and the emergence of respiratory proteins

Abstract: The velvet worms (Onychophora) are considered living fossils and are closely related to the Euarthropoda. Onychophora possess a tracheal system for respiratory function, but oxygen-transport proteins have been considered unnecessary. Here, we show that the hemolymph of the Epiperipatus sp. (Onychophora: Peripatidae) contains an arthropod-type hemocyanin, demonstrating that such protein exists outside the Euarthropoda. Thus, the evolution of oxygen carriers preceded the divergence of the Onychophora and Euarthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 38 publications
(36 reference statements)
3
41
0
Order By: Relevance
“…Together with molecular datasets (e.g. Boore et al 1998;Shultz & Regier 2000;Giribet et al 2001;Kusche et al 2002;Pisani et al 2004;Petrov & Vladychenskaya 2005;Regier et al 2005;Mallatt & Giribet 2006), these studies contributed considerably to the new discussion on arthropod relationships (e.g. Whitington & Bacon 1997;Dohle 2001;Richter 2002;Whitington 2004;Giribet et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Together with molecular datasets (e.g. Boore et al 1998;Shultz & Regier 2000;Giribet et al 2001;Kusche et al 2002;Pisani et al 2004;Petrov & Vladychenskaya 2005;Regier et al 2005;Mallatt & Giribet 2006), these studies contributed considerably to the new discussion on arthropod relationships (e.g. Whitington & Bacon 1997;Dohle 2001;Richter 2002;Whitington 2004;Giribet et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although the phylogenetic position of onychophorans is still debated, many phylogenies group them with euarthropods and possibly tardigrades in the phylum Arthropoda; thus onychophorans share a common ancestor with euarthropods (8,(19)(20)(21)(22)(23). Analyses of neurogenesis in onychophorans suggests that, similar to insects and crustaceans, single neural precursors are formed in the neuroectoderm, rather than groups of cells as seen in chelicerates and myriapods (24)(25)(26).…”
mentioning
confidence: 99%
“…Previous phylogenetic reconstructions between mollusc and arthropod type-3 copper genes have indicated that these proteins have evolved independently (Burmester and Scheller 1996, Decker and Terwilliger 2000, Burmester 2002, Kusche et al 2002. Here, I demonstrated that mollusc and arthropod type-3 copper genes belong to different subclasses (α-and ÎČ-subclass, respectively), supporting previous assertions of their independent origin and convergent evolution.…”
Section: Structural Comparison Of Type-3 Copper Protein Active Sites supporting
confidence: 85%